2019
DOI: 10.1186/s12883-019-1571-4
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting the in-hospital mortality after large hemispheric infarction

Abstract: BackgroundLarge hemispheric infarction (LHI) is a severe form of stroke with high mortality and disability rates. The purpose of this study was to explore predictive indicators of the in-hospital mortality of LHI patients treated conservatively without decompressive hemicraniectomy.MethodWe performed a retrospective study of 187 consecutive patients with LHI between January 1, 2016 to May 31, 2019. The receiver operating curves were preformed to evaluate predictive performance of demographics factors, biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…It can help clinicians make quick and sound decisions due to the characteristics of better accuracy, straightforward digital interfaces and readily comprehensible prognosis. 30 , 31 To the best of our knowledge, this is the first study to construct a nomogram for predicting the risk of in-hospital mortality in the NICU, which simply and easily depicted the associations of each predictor with in-hospital mortality risk. Moreover, the AUC of the present nomogram in predicting neonatal in-hospital mortality was 0.865, showing good predictive accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…It can help clinicians make quick and sound decisions due to the characteristics of better accuracy, straightforward digital interfaces and readily comprehensible prognosis. 30 , 31 To the best of our knowledge, this is the first study to construct a nomogram for predicting the risk of in-hospital mortality in the NICU, which simply and easily depicted the associations of each predictor with in-hospital mortality risk. Moreover, the AUC of the present nomogram in predicting neonatal in-hospital mortality was 0.865, showing good predictive accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used the midline shift to predict AIS patients' prognoses. Sun et al revealed that midline shift was an independent predictor of in-hospital mortality in patients with large hemispheric infarctions [17] . McKeown et al concluded that the presence of a midline shift was predictive of poor outcomes [18] .…”
Section: Discussionmentioning
confidence: 99%
“…However, both local and overseas studies have rarely focused on VLBW infants, and no risk prediction model has been established thus far. In recent times, the nomogram is widely used as a simple statistical visual tool for predicting the occurrence, development, and prognosis of various diseases ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%